Conductive composite binder, sodium ion battery negative electrode containing conductive composite binder and battery
By mixing the sodium (3-sulfonate)acrylic acid-3-sulfonate-acrylic acid copolymer with natural polysaccharides to prepare conductive composite binders, the problem of slow migration speed of hard carbon anode Na+ and insufficient cohesion of the binder in sodium ion batteries is solved, efficient electrode bonding and ion conduction are achieved, and the rate performance and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202411602882.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-14
AI Technical Summary
In existing sodium ion batteries, the Na+ migration speed of the hard carbon anode is slow, resulting in limited rate performance, and the cohesion and adhesion of existing adhesives are not sufficient to support the adhesion needs of amorphous carbon.
The conductive composite adhesive is prepared by mixing poly(meth)acrylic acid-3-sulfonate sodium-acrylic copolymer with natural polysaccharide to form an elastic conductive network and improve the adhesive force and ion conductivity of the adhesive.
The bonding force and ionic conductivity of the negative electrode sheet of the sodium ion battery are improved, the rate performance and cycle stability of the electrode are enhanced, and the overall performance of the battery is improved.
Smart Images

Figure BDA0005128759800000131 
Figure BDA0005128759800000171
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries. Specifically, the present invention relates to a conductive composite binder that can be used to prepare a negative electrode of a sodium ion battery. The present invention also relates to a poly (meth) acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer contained in the conductive composite binder, a negative electrode sheet of a sodium ion battery containing the conductive composite binder, and a sodium ion battery containing the negative electrode sheet. Background Art
[0002] With the rapid development of the economy, the pressure of non-renewable energy consumption is increasing year by year. Green and sustainable clean energy is attracting more and more attention and research. Lithium-ion batteries (LIBs) are the most widely used electrochemical energy storage system, but the high cost of lithium resources and limited lithium reserves have become key issues restricting the development of the industry. Therefore, it is urgent to develop low-cost and high-performance battery systems.
[0003] Sodium-ion batteries (SIBs) have the advantages of low cost and the abundant and widespread sodium reserves they use. At the same time, sodium and lithium belong to the same main group in the periodic table, so they have similar chemical properties and parallel working principles, which means that rechargeable SIBs will be a suitable alternative to LIBs.
[0004] In the application of SIBs, binders, as electrode materials, play a vital role in maintaining electrode integrity and preserving electron / ion transfer, which directly affects the capacity, life, and safety of batteries.
[0005] Based on the experience of LIBs, the application of binders in SIBs mainly focuses on the development of new binders that can suppress the volume expansion of electrodes. However, this experience cannot solve the irreversible side reactions at the interface and the slow Na+ conversion of hard carbon (HC) anodes. + Migration. Compared with the graphite anode of LIBs, the HC anode of SIBs has a larger specific surface area and more defects, which often leads to a low first coulombic efficiency. In addition, due to the large ionic radius and atomic mass of elemental Na, the diffusion kinetics are slow, and the rate performance of the HC anode is limited. In addition, the main binder system of LIBs (styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC)) is limited by the point structure of the material itself, and its cohesion and adhesion are not enough to support the adhesion requirements of amorphous carbon. Therefore, there is an urgent need to rationally design new multifunctional binders to break through the bottleneck of the HC anode of SIBs.
[0006] CN117467380A discloses a binder for sodium ion batteries and a preparation method thereof. The polymer modified resin prepared by the binder can improve the embedding integrity of the internal structure of the modified resin through the compounding reaction between different monomers, further improve the structural stability of the modified resin, and is particularly suitable for bonding sodium ion batteries. The binder is mainly developed for graphite anodes, and the mechanism of action of HC anode binders has not been explored.
[0007] CN117186812A discloses an aqueous copolymer binder, a preparation method and a negative electrode material for a sodium ion battery. The performance of the aqueous copolymer binder is controllable, and it can effectively improve the cycle stability of the negative electrode material of the battery, so that the electrode maintains its integrity and has good electrical connectivity. Although the combination of a polysaccharide binder and a polyacrylic acid binder can provide good bonding force, it limits the rate performance of the battery to a certain extent.
[0008] CN116656277A discloses a binder, a negative electrode sheet and a sodium ion battery. The binder is a copolymer of repeating units derived from acrylic acid monomers, repeating units derived from acrylamide monomers and repeating units derived from dopamine acrylic acid, and has carboxyl, amino and hydroxyl structures, which can improve the cycle performance, stability performance and rate performance of sodium ion batteries. However, the binder enhances the migration rate of sodium ions through carboxyl groups, and cannot effectively improve the ionic conductivity of the binder.
[0009] Therefore, there is still a need in the prior art for a binder for a negative electrode sheet of a sodium ion battery having excellent bonding strength and ion conductivity. Summary of the invention
[0010] Purpose of the Invention
[0011] In view of the problems existing in the prior art described in the above background technology section, the object of the present invention is to provide a conductive composite binder that can be used to prepare a negative electrode sheet of a sodium ion battery. The object of the present invention is also to provide a poly (meth) acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer contained in the conductive composite binder, as well as to provide a negative electrode sheet of a sodium ion battery containing the conductive composite binder and a sodium ion battery containing the negative electrode sheet.
[0012] Technical Solution
[0013] In order to achieve the above object, the present invention adopts the following technical solutions:
[0014] Scheme 1: Sodium poly(meth)acrylic acid-3-sulfonic acid propyl ester-acrylic acid copolymer, wherein the copolymer comprises:
[0015] A monomer unit of formula (I) derived from sodium 3-sulfonyl (meth)acrylate, and
[0016] The monomer unit of formula (II) derived from an acrylic acid compound:
[0017] -(CH2-C(A)(R'))- (I)
[0018] -(CH2-CH(R))- (II)
[0019] in,
[0020] A represents the group -COO-(CH2CH2CH2)-SO3 - Na + ,
[0021] R', independently of one another and identically or differently, represents on each occurrence hydrogen or a methyl group;
[0022] R, independently of one another and identically or differently, represents on each occurrence a carboxylic acid group, an amide group or a cyano group;
[0023] in
[0024] In the poly (meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer, the molar ratio of the monomer unit of formula (I) to the monomer unit of formula (II) is in the range of about 1:(0.2-5).
[0025] Option 2: The copolymer according to Option 1 above, wherein the copolymer has a weight average molecular weight in the range of about 10,000 to about 2,000,000 g / mol.
[0026] Scheme 3: The copolymer according to Scheme 1 or 2 above, wherein the copolymer is a random copolymer, a block copolymer or an alternating copolymer.
[0027] Scheme 4: A method for preparing the copolymer according to any one of Schemes 1 to 3, wherein the method comprises: subjecting an aqueous solution containing sodium 3-sulfonyl (meth)acrylate and an acrylic monomer to polymerization reaction with the addition of an initiator.
[0028] Scheme 5: The preparation method according to Scheme 4 above, wherein the acrylic monomer comprises one or more of acrylic acid, acrylamide and acrylonitrile.
[0029] Scheme 6: The preparation method according to Scheme 4 or 5 above, wherein the molar ratio of the sodium (meth)acrylate-3-sulfonate propyl ester to the acrylic acid monomer is in the range of about 1:(0.2-5).
[0030] Scheme 7: The preparation method according to any one of Schemes 4 to 6 above, wherein the solid content of the aqueous solution containing sodium 3-sulfonyl (meth)acrylate and acrylic acid monomer is in the range of about 10 to about 40 weight %.
[0031] Scheme 8: The preparation method according to any one of schemes 4 to 7 above, wherein the pH value of the aqueous solution containing sodium 3-sulfonyl (meth)acrylate and acrylic acid monomers is in the range of about 6 to about 9.
[0032] Scheme 9: The preparation method according to any one of Schemes 4 to 8 above, wherein the polymerization reaction is carried out at a temperature of about 60 to about 80° C. for about 4 to about 10 hours.
[0033] Scheme 10: The preparation method according to any one of Schemes 4 to 9 above, wherein the initiator comprises one or more of ammonium persulfate, sodium persulfate and hydrogen peroxide.
[0034] Scheme 11: The preparation method according to any one of schemes 4 to 10, wherein the amount of the initiator used is about 8 to about 15 wt % based on the weight of the acrylic monomer.
[0035] Scheme 12: A conductive composite adhesive, wherein the conductive composite adhesive comprises:
[0036] Natural polysaccharides,
[0037] The sodium poly(meth)acrylate-3-sulfonate propyl ester-acrylic acid copolymer according to any one of the above schemes 1 to 3, or the sodium poly(meth)acrylate-3-sulfonate propyl ester-acrylic acid copolymer prepared by the preparation method according to any one of the above schemes 4 to 11, and
[0038] water,
[0039] The weight ratio of the natural polysaccharide to the sodium poly(meth)acrylic acid-3-sulfonate propyl ester-acrylic acid copolymer is in the range of about (5-15):(1-3).
[0040] Option 13: According to the conductive composite adhesive described in Option 12 above, the natural polysaccharide comprises one or more of sodium alginate, gum arabic and guar gum.
[0041] Scheme 14: The conductive composite adhesive according to Scheme 12 or 13, wherein the weight average molecular weight of the natural polysaccharide is in the range of about 50,000 to about 800,000 g / mol.
[0042] Aspect 15: The conductive composite adhesive according to any one of aspects 12 to 14, wherein the conductive composite adhesive has a solid content in the range of about 6 wt % to about 12 wt %.
[0043] Option 16: A negative electrode sheet for a sodium ion battery, wherein the negative electrode sheet comprises a negative electrode current collector, a negative electrode material, a conductive agent and a conductive composite binder according to any one of the above options 12 to 15, and the amount of the conductive composite binder used is about 1 weight % to about 5 weight % based on the total weight of the negative electrode material, the conductive agent and the binder.
[0044] Option 17: A sodium ion battery, wherein the sodium ion battery comprises a negative electrode sheet according to Option 16 above.
[0045] Technical Effects
[0046] The invention obtains a conductive composite adhesive by mixing a natural polysaccharide adhesive with a conductive self-doped poly (methyl) acrylic acid-3-sodium sulfonate propyl ester-acrylic acid copolymer, thereby forming an elastic conductive network.
[0047] Natural polysaccharide binders are rich in carboxyl and hydroxyl groups, which can promote the formation of hydrogen bonds under protonation and play an important role in providing bonding force to maintain the bond network within the electrode. For HC porous anode materials, natural polysaccharide binders can fill the unfavorable pores on the surface of the porous material, thereby reducing the consumption of the SEI film and improving the initial Coulomb efficiency. Natural polysaccharide binders not only make the active particles and conductive agents evenly distributed, effectively alleviating the agglomeration of active materials, but also facilitate the penetration of electrolytes due to their good wettability. Therefore, during the charge and discharge process, the active material can maintain close contact with the collector to ensure the integrity of the electrode structure during the cycle.
[0048] The binder components such as sodium alginate (SA) and the HC anode in the binder of the present invention contain hydroxyl and carboxyl groups, so a uniform passivation film can be formed by hydrogen bonding or esterification between functional groups. In addition, the SA binder rich in carboxyl groups has an electrostatic repulsion effect, which reduces the agglomeration effect between small molecules and makes the binder easy to wet, thereby uniformly covering the surface of carbon particles. However, the uniform passivation film lacks an effective ion diffusion path, which reduces the transfer rate of ions from the interface to the inside of the carbon particles.
[0049] The binder of the present invention contains a poly (meth) acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer, wherein the carboxyl and / or sulfonate groups from the (meth) acrylic acid-3-sulfonic acid propyl sodium ester monomer unit and the acrylic acid monomer unit can form hydrogen bonds, ionic bonds or condensation to form esters, etc., thereby achieving cross-linking to form an elastic network. The carboxyl group can bond with the hydroxyl (-OH) in the natural polysaccharide binder to improve the flexibility of the conductive composite binder, and can also bond with the hydroxyl and carboxyl groups on the surface of the HC anode to improve the adhesion of the electrode. The abundant carboxyl and carbonyl groups can form a wetting effect on the surface of the current collector such as aluminum foil, produce chemical bonds with the aluminum surface, form hydrogen bonds, and improve the adhesion of the HC anode to the foil substrate; the terminal sulfonic acid group can be reversibly cross-linked with other sulfonic acid groups through electrostatic action, and the sulfonic acid group also has a movable Na + , promoting ion transport within the polymer matrix via carrier and surface hopping mechanisms, resulting in high sodium ion conductivity. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without paying creative work belong to the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on normal conditions.
[0051] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. The term "about" used in the present invention means that the modified numeral can fluctuate within the range of ±20%, ±15%, ±10%, ±5% or ±2% of the numeral. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in the present invention.
[0052] According to a first aspect of the present invention, the present invention provides a sodium poly(meth)acrylic acid-3-sulfonatepropyl ester-acrylic acid copolymer.
[0053] The poly(meth)acrylic acid-3-sulfonic acid sodium propyl ester-acrylic acid copolymer according to the first aspect of the present invention comprises a monomer unit of formula (I) derived from sodium 3-sulfonic acid propyl (meth)acrylic acid ester and a monomer unit of formula (II) derived from an acrylic acid compound:
[0054] -(CH2-C(A)(R'))- (I)
[0055] -(CH2-CH(R))-(II)
[0056] in,
[0057] A represents the group -COO-(CH2CH2CH2)-SO3 - Na + ,
[0058] R', independently of one another and identically or differently, represents on each occurrence hydrogen or a methyl group; and
[0059] R, independently of one another and identically or differently, represents on each occurrence a carboxylic acid group, an amide group or a cyano group.
[0060] In the poly(methyl)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer according to the first aspect of the present invention, the molar ratio of the monomer unit of formula (I) to the monomer unit of formula (II) is in the range of about 5:1 to about 1:5, that is, in the range of about 1:(0.2-5), such as about 1:4, about 1:3, about 1:2, about 1:1, about 2:1, about 3:1 or about 4:1. Here, the molar ratio of the monomer unit of formula (I) to the monomer unit of formula (II) should not be too large, for example, it should not be greater than about 5:1, otherwise it will affect the bonding effect of the binder and reduce the stability of the electrode structure. At the same time, the molar ratio should not be too small, for example, it should not be less than about 1:5, otherwise it will increase the impedance of the binder, resulting in large electrode polarization and reduced cycle performance.
[0061] In a preferred embodiment of the first aspect of the invention, the sodium poly(meth)acrylic acid-3-sulfonate propyl ester-acrylic acid copolymer has a weight average molecular weight in the range of about 10,000 to about 2,000,000 g / mol, for example, about 100,000 g / mol, about 200,000 g / mol, about 400,000 g / mol, about 600,000 g / mol, about 800,000 g / mol, about 1,000,000 g / mol, about 1,200,000 g / mol, about 1,500,000 g / mol or about 1,800,000 g / mol. Here, the molecular weight of the copolymer should not be too large, for example, it should not be greater than about 2,000,000 g / mol, otherwise the binder may find it difficult to wet the material surface and the slurry stability may also deteriorate. At the same time, the molecular weight should not be too small, for example, it should not be less than about 10,000 g / mol, otherwise the bonding force of the binder may be insufficient.
[0062] In another preferred embodiment of the first aspect of the present invention, the form of the sodium poly(meth)acrylate-3-sulfonatepropyl ester-acrylic acid copolymer is not particularly limited, for example, it can be a random copolymer, a block copolymer or an alternating copolymer.
[0063] According to the second aspect of the present invention, the present invention provides a method for preparing the poly (meth)acrylic acid-3-sulfonate propyl sodium ester-acrylic acid copolymer as described above according to the first aspect of the present invention.
[0064] The preparation method according to the second aspect of the present invention comprises subjecting an aqueous solution containing sodium 3-sulfonyl (meth)acrylate and an acrylic acid monomer to a polymerization reaction in the presence of an initiator. The raw materials and conditions of the polymerization reaction are described in detail below.
[0065] Sodium 3-sulfonate propyl (meth)acrylate:
[0066] The sodium (meth)acrylate-3-sulfonate propyl ester can be obtained commercially, or can be obtained by replacing the potassium ions in potassium (meth)acrylate-3-sulfonate propyl ester with sodium ions. Specifically, in a preferred embodiment of the present invention, the preparation can be carried out with reference to the method disclosed in Chinese patent application CN 109574042 A, which is incorporated into the present invention by reference in its entirety.
[0067] For example, the sodium 3-sulfonate propyl (meth)acrylate can be prepared by the following process: dissolving potassium salt of 3-sulfonate propyl (meth)acrylate in deionized water to form a solution of about 10 to about 20 wt%, adding sodium perchlorate in a molar amount of about 1 to about 6 times that of the potassium salt, reacting at a heated temperature (e.g., about 80° C.), and maintaining the temperature for about 1 to about 3 hours, cooling after the reaction is completed, and obtaining a potassium perchlorate solid and an aqueous solution of sodium salt of 3-sulfonate propyl (meth)acrylate after liquid-solid separation. The obtained solution of sodium salt of 3-sulfonate propyl (meth)acrylate can be evaporated to remove the solvent to obtain the sodium salt solid, or can be directly used for subsequent copolymerization without separation.
[0068] Acrylic monomers:
[0069] The acrylic monomer includes but is not limited to one or more of acrylic acid, acrylamide and acrylonitrile, and acrylic acid or acrylonitrile is most preferred.
[0070] Initiator:
[0071] There is no particular limitation on the compound used as the initiator, as long as it can release free radicals under appropriate conditions and initiate the copolymerization of the sodium (meth)acrylate-3-sulfonate propyl ester and the acrylic monomer. For example, in some embodiments of the present invention, one or more of ammonium persulfate, sodium persulfate and hydrogen peroxide can be used as the initiator.
[0072] In the copolymerization process of the sodium (meth) acrylate-3-sulfonic acid propyl ester and the acrylic monomer, the amount of the initiator is preferably about 8 to about 15 weight %, such as about 9 weight %, about 10 weight %, about 11 weight %, about 12 weight %, about 13 weight % or about 14 weight %, based on the weight of the acrylic monomer. Here, the amount of the initiator should not be too large or too small, for example, it should not exceed about 15 weight % of the weight of the acrylic monomer, nor should it be less than about 8 weight % of the weight of the acrylic monomer, otherwise the molecular weight of the reaction product may be too large or too small and not within the required range of about 10,000 to about 2,000,000 g / mol.
[0073] Polymerization conditions:
[0074] During the copolymerization of the sodium 3-sulfonyl (meth)acrylate and the acrylic monomer, the molar ratio of the sodium 3-sulfonyl (meth)acrylate and the acrylic monomer is in the range of about 5:1 to about 1:5, that is, in the range of about 1:(0.2-5), for example, about 1:4, about 1:3, about 1:2, about 1:1, about 2:1, about 3:1 or about 4:1.
[0075] In the copolymerization process of the sodium salt of 3-sulfonyl (meth)acrylate and the acrylic monomer, the acrylic monomer is first added to the aqueous solution of the sodium salt of 3-sulfonyl (meth)acrylate under an inert atmosphere, such as a nitrogen or argon atmosphere, and the solid content of the aqueous solution containing the sodium salt of 3-sulfonyl (meth)acrylate and the acrylic monomer is controlled to be in the range of about 10 to about 40 weight %, such as 20 weight % or about 30 weight %, wherein the pH value of the aqueous solution of the sodium salt of 3-sulfonyl (meth)acrylate and the acrylic monomer is adjusted to be in the range of about 6 to about 9, such as pH=about 7 or pH=about 8. Here, the solid content of the aqueous solution should not be too large, such as not more than about 40 weight %, otherwise the molecular weight of the reaction product may be too large; nor should it be too small, such as not less than about 10 weight %, otherwise the copolymerization reaction effect is not good. In addition, the pH value of the aqueous solution should not be too high or too low, for example, the pH value should not be higher than about 9 or lower than about 6, otherwise it may lead to poor stability of the polymer and poor copolymerization effect.
[0076] After preparing the aqueous solution of the sodium (meth)acrylate-3-sulfonate propyl ester and the acrylic monomer, an initiator is added. Here, the initiator can be added all at once or gradually, for example, the catalyst can be added at a rate of about 3 to about 5 g / min (e.g., about 4 g / min). Here, the catalyst addition rate should not be too fast, for example, should not exceed about 5 g / min, otherwise the reaction may occur in a concentrated manner and at a fast rate, and the molecular weight of the reaction product may be too large; it should not be too slow, for example, should not be less than about 3 g / min, otherwise the copolymerization reaction effect may be poor.
[0077] The copolymerization process of the sodium 3-sulfonyl (meth)acrylate and the acrylic monomer is preferably carried out at a temperature of about 60 to about 80° C. (e.g., about 70° C.) for about 4 to about 10 hours, such as about 5 hours, about 6 hours, about 7 hours, about 8 hours or about 9 hours.
[0078] After the copolymerization of the sodium (meth)acrylate-3-sulfonic acid propyl ester and the acrylic acid monomer is completed, the obtained copolymer solution is vacuum dried to remove the solvent, and the obtained copolymer solid is washed with ethanol and filtered and dried to obtain the sodium poly (meth)acrylate-3-sulfonic acid propyl ester-acrylic acid copolymer.
[0079] According to a third aspect of the present invention, the present invention provides a conductive composite adhesive.
[0080] The conductive composite adhesive according to the third aspect of the present invention comprises a natural polysaccharide, a poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer as described in the first aspect of the present invention, or a poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer prepared by the preparation method described in the second aspect of the present invention, and water. The following describes in detail each component contained in the conductive composite adhesive.
[0081] Sodium poly(meth)acrylate-3-sulfonic acid propyl ester-acrylic acid copolymer:
[0082] The poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer contained in the conductive composite adhesive of the third aspect of the present invention is the copolymer described in the first aspect of the present invention or the copolymer prepared by the preparation method described in the second aspect of the present invention. The characteristics and preferred sub-characteristics described for the copolymer in the first and second aspects of the present invention are all applicable to the copolymer in the conductive composite adhesive of the third aspect of the present invention.
[0083] Natural polysaccharides:
[0084] In the conductive composite adhesive of the third aspect of the present invention, the natural polysaccharide contained is not particularly limited, as long as it has sufficient carboxyl and hydroxyl groups to achieve cross-linking with the carboxyl groups carried by or formed by the copolymer of the first aspect of the present invention. However, in some preferred embodiments of the present invention, the natural polysaccharide comprises one or more of sodium alginate, gum arabic and guar gum.
[0085] In some other preferred embodiments, the natural polysaccharide has a weight average molecular weight in the range of about 50,000 to about 800,000 g / mol, for example, about 100,000 g / mol, about 200,000 g / mol, about 400,000 g / mol or about 600,000 g / mol. Here, the molecular weight of the natural polysaccharide should not be too large, for example, it should not exceed about 800,000 g / mol, otherwise the binder is difficult to wet the material surface and the slurry stability is poor; it should not be less than about 50,000 g / mol, otherwise the binding force of the binder is insufficient.
[0086] In the conductive composite adhesive of the third aspect of the present invention, the weight ratio of the natural polysaccharide to the sodium poly(meth)acrylic acid-3-sulfonic acid propyl ester-acrylic acid copolymer is in the range of about (5-15): (1-3), such as about 2:1, about 4:1, about 6:1, about 8:1, about 10:1, about 12:1 or about 14:1. Here, the weight ratio of the natural polysaccharide to the sodium poly(meth)acrylic acid-3-sulfonic acid propyl ester-acrylic acid copolymer should not be too large, such as not exceeding 15:1, otherwise the ionic conductivity of the adhesive will be limited; nor should it be too small, such as not less than 5:3, otherwise the bonding force of the obtained composite adhesive cannot be maintained at a high level. Most preferably, the weight ratio of the natural polysaccharide to the sodium poly(meth)acrylic acid-3-sulfonic acid propyl ester-acrylic acid copolymer is about 8:1, at which the adhesive has stronger bonding strength and better ionic conductivity.
[0087] In a preferred embodiment of the third aspect of the present invention, the conductive composite adhesive has a solid content in the range of about 6 wt % to about 12 wt %, for example, about 8 wt % or about 10 wt %. Here, the solid content of the conductive composite adhesive should not be too large, for example, should not exceed about 12 wt %, otherwise it may affect the dispersion effect of the slurry during the homogenization process; nor should it be too small, for example, should not be less than about 6 wt %, otherwise it is difficult to design a matching slurry solid content.
[0088] The conductive composite adhesive of the third aspect of the present invention can be obtained by uniformly mixing the aqueous solution of the natural polysaccharide and the aqueous solution of the poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer. For example, in a preferred embodiment of the present invention, the natural polysaccharide is first added to water, stirred until completely dissolved, and prepared into a natural polysaccharide aqueous solution with a concentration of about 1% by weight to about 10% by weight, cooled to room temperature (e.g., about 25±5° C.) and kept constant at this temperature, and then the aqueous solution of the poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid polymer obtained as described above is added, stirred at high speed for about 4 to about 6 hours until it is uniformly dispersed, and sieved after cooling to room temperature to obtain an emulsion adhesive. The obtained emulsion adhesive preferably has a solid content in the range of about 6% by weight to about 12% by weight.
[0089] According to a fourth aspect of the present invention, the present invention provides a negative electrode sheet for a sodium ion battery.
[0090] The sodium ion battery negative electrode sheet of the fourth aspect of the present invention comprises a conductive composite binder, a negative electrode material and a conductive agent as described in the third aspect of the present invention. The negative electrode material includes but is not limited to soft carbon, hard carbon, mesophase carbon microspheres, artificial graphite, natural graphite, silicon carbon, silicon oxygen, micron silicon particles, silicon nanowires, carbon-encapsulated silicon particles, silicon-based alloy powder, and one or more of tin dioxide particles. The conductive agent includes but is not limited to one or more of conductive graphite, conductive carbon black, carbon nanotubes, vapor-grown carbon fibers (VGCF), graphene, and composite fibers.
[0091] In a preferred embodiment of the sodium ion battery electrode sheet of the fourth aspect of the invention, the amount of the conductive composite binder is about 1 wt % to about 5 wt %, for example about 2 wt %, 3 wt % or about 4 wt %, based on the total weight of the negative electrode material, the conductive agent and the binder.
[0092] In an exemplary embodiment, the negative electrode sheet can be prepared by the following process: after the negative electrode material and the conductive agent are evenly mixed, an emulsion solution of the conductive composite binder in deionized water is added to the obtained mixture, and if necessary, the temperature is raised to about 30 to about 50° C. and stirred at this temperature for, for example, about 4 to about 6 hours to enhance the dispersion effect of the binder, and after cooling to room temperature, the obtained mixture is coated on an aluminum current collector, and after drying and rolling treatment, vacuum drying at a temperature of about 80 to about 100° C. for about 8 to about 16 hours to obtain the sodium ion battery negative electrode sheet of the present invention.
[0093] According to a fifth aspect of the present invention, the present invention provides a sodium ion battery.
[0094] The sodium ion battery of the fifth aspect of the present invention comprises the negative electrode sheet as described above in the fourth aspect of the present invention.
[0095] For example, in a preferred embodiment, the sodium ion battery further comprises a positive electrode, a separator and an electrolyte in addition to the negative electrode as described above. The positive electrode may preferably include an oxide, polyanion, Prussian blue, or organic sodium ion positive electrode material.
[0096] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0097] The raw materials used in the following examples and comparative examples are all commercially available analytically pure products.
[0098] Examples 1 to 6: General preparation method of conductive composite adhesive
[0099] The specific raw materials and process conditions used in each example are shown in Table 1 below.
[0100] (1) Preparation of sodium 3-sulfonate propyl (meth)acrylate:
[0101] At room temperature, potassium salt of (meth)acrylic acid-3-sulfonic acid propyl ester is dissolved in deionized water to form a potassium salt solution with a concentration of about 15% by weight, sodium perchlorate is added thereto, and the molar ratio of sodium perchlorate to the potassium salt is controlled to be about 3:1, and the mixture is heated to about 80° C. and reacted for about 3 hours. After cooling, solid-liquid separation is performed to obtain a potassium perchlorate solid and an aqueous solution with a concentration of about 15% by weight of sodium salt of (meth)acrylic acid-3-sulfonic acid propyl ester.
[0102] (2) Preparation of sodium poly(meth)acrylic acid-3-sulfonic acid propyl ester-acrylic acid copolymer:
[0103] Under nitrogen, the sodium salt aqueous solution obtained in the above step (1) is added to a reaction kettle, and acrylic acid monomer and pure water are added and mixed uniformly. The pH value of the aqueous solution is adjusted to about 8, and the solid content of the whole solution is controlled to be about 30% by weight, wherein the molar ratio of the sodium salt to the acrylic acid monomer is as shown in Table 1. After the reactants are heated to about 70° C., about 8% by weight of sodium persulfate based on the weight of the acrylic acid is added at a rate of about 4 g / min, and the reaction is carried out for the time as shown in Table 1. After the reaction is completed, the obtained copolymer solution is vacuum dried to remove the water as a solvent, and the obtained copolymer solid is washed with anhydrous ethanol, filtered and freeze-dried to obtain poly (meth)acrylic acid-3-sulfonic acid propyl ester sodium-acrylic acid copolymer, and the weight average molecular weight of the obtained copolymer is measured, and the results are shown in the following Table 1.
[0104] (3) Preparation of conductive composite adhesive:
[0105] Sodium alginate with a weight average molecular weight of about 100,000 g / mol is added to water to prepare a sodium alginate aqueous solution with a concentration of about 7% by weight. The aqueous solution is cooled to room temperature, and the poly (meth) acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer prepared in the above step (2) is added, wherein the weight ratio of the natural polysaccharide to the copolymer is shown in Table 1 below. The mixture is stirred at high speed for about 4 to about 6 hours until it is uniformly dispersed, cooled to room temperature, and sieved to obtain an emulsion-like binder with a solid content of about 8% by weight.
[0106] Table 1
[0107]
[0108] Comparative Example 1
[0109] Sodium alginate with a weight average molecular weight of about 100,000 g / mol is added to water to prepare a sodium alginate aqueous solution with a concentration of about 7% by weight. The aqueous solution is cooled to room temperature, and a polyacrylic acid homopolymer with a weight average molecular weight of about 1,000,000 g / mol is added, wherein the weight ratio of sodium alginate to polyacrylic acid homopolymer is about 8:1. Stir at high speed for about 4 to about 6 hours until uniform dispersion, cool to room temperature and sieve to obtain an emulsion-like binder with a solid content of about 8% by weight.
[0110] Comparative Example 2
[0111] An aqueous solution of sodium alginate with a solid content of about 8% by weight and a weight average molecular weight of about 100,000 g / mol is stirred at high speed for about 4 to about 6 hours until it becomes uniform, cooled to room temperature, and sieved to obtain an emulsion binder.
[0112] Comparative Example 3
[0113] An aqueous solution of a poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer with a solid content of about 8% by weight and a weight average molecular weight of about 1,000,000 g / mol is stirred at high speed for about 4 to about 6 hours until it is uniformly dispersed, cooled to room temperature, and sieved to obtain an emulsion adhesive.
[0114] Comparative Example 4
[0115] A conductive composite adhesive was prepared in a similar process to Example 1, except that the molar ratio of sodium salt:acrylic monomer was adjusted to about 10:1.
[0116] Comparative Example 5
[0117] A conductive composite adhesive was prepared in a similar process to Example 1, except that the molar ratio of sodium salt: acrylic monomer was adjusted to about 1:10.
[0118] Comparative Example 6
[0119] A conductive composite adhesive was prepared in a similar process to Example 1, except that the weight ratio of natural polysaccharide:copolymer was adjusted to about 1:1.
[0120] Comparative Example 7
[0121] A conductive composite adhesive was prepared in a similar process to Example 1, except that the weight ratio of natural polysaccharide:copolymer was adjusted to about 20:1.
[0122] Preparation of sodium ion battery negative electrode:
[0123] The conductive composite binders of Examples 1-6 and Comparative Examples 1-7 are used to prepare negative electrode sheets, respectively, specifically comprising: after uniformly mixing about 96 parts by weight of hard carbon (negative electrode active material) with about 1 part by weight of Super P conductive carbon black (conductive agent) for about 30 minutes, adding about 1.5 parts by weight (in terms of solid) of the conductive composite binder, the conductive composite binder being in the form of a conductive composite binder aqueous solution with a solid content of about 4% by weight. Deionized water is added to control the kneading solid content of the obtained negative electrode material to be in the range of about 65% by weight to about 69% by weight. The negative electrode material is kneaded for about 60 minutes. Continue to add about 1.5 parts by weight (in terms of solid) of the conductive composite binder and deionized water, control the slurry viscosity to be in the range of 5000±2000mPa·s, and continue to disperse at high speed for about 3 hours. The material is sieved through a 200-mesh sieve to obtain a negative electrode slurry with a solid content of about 45% by weight to about 55% by weight. The negative electrode slurry is uniformly coated on the aluminum foil as the negative electrode current collector, and the single-sided coating density is about 50 g / m 2 , and the negative electrode sheet is obtained through baking and rolling.
[0124] Assembly of sodium-ion batteries:
[0125] The negative electrode sheets are respectively assembled with the positive electrode sheets into a battery cell, wherein the positive electrode sheets are prepared using sodium nickel iron manganese oxide positive electrode materials. A soft-pack sodium ion battery is manufactured using a soft-pack lamination process. The positive electrode sheets, the negative electrode sheets and a polyethylene diaphragm (e.g., PE+OBS diaphragm) are laminated and assembled, and then baked until the moisture content is qualified, and an electrolyte is injected, and then the battery is packaged after hot pressing and high-temperature standing, and then the soft-pack finished battery is obtained by standing at room temperature after volume division. The electrolyte used is a conventional electrolyte in the art, and the solvents it contains are ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), wherein EC:PC:EMC:DMC=about 20:10:50:20, the sodium salts it contains are sodium hexafluorophosphate (NaPF6, with a concentration of about 14 weight %) and sodium bis(fluorosulfonyl)imide (NaFSI, with a concentration of about 3 weight %), and the additives it contains are vinylene carbonate (VC, with a concentration of about 0.8 weight %), fluoroethylene carbonate (FEC, with a concentration of about 3 weight %), vinyl sulfate (DTD, with a concentration of about 0.3 weight %) and 1,3-propane sultone (1-3PS, with a concentration of about 0.3 weight %).
[0126] Performance Testing
[0127] (1) Negative electrode stripping force test:
[0128] A negative electrode sheet prepared by the conductive composite binder of Examples 1 to 6 and Comparative Examples 1 to 7 was prepared. According to the ASTM-D903 test method, the negative electrode sheet was peeled off at a rate of about 10 mm / min and an angle of about 180°. The peeling force of the negative electrode sheet was tested. The test results are shown in Table 2 below.
[0129] (2) First Coulomb efficiency test:
[0130] The adopted capacity division voltage range is about 2.0V to about 4.0V, and the battery's first coulombic efficiency = discharge capacity of the first cycle of capacity division / (formation charging capacity + charging capacity of the first cycle of capacity division) × 100%. The test results are shown in Table 2 below.
[0131] (3) DC internal resistance DCR test:
[0132] The battery was tested on an electrochemical workstation battery testing system at about 25°C. The battery capacity was adjusted to 50% SOC and left for about 2 hours. The end-of-standing voltage U1 was recorded. The battery was discharged at a current of I (2C) for about 10 seconds, and the end-of-discharge voltage U2 was recorded. DCR was calculated to be (U1-U2) / I. The test results are shown in Table 2 below.
[0133] (4) High temperature cycle test:
[0134] The finished batteries prepared with the binders of Examples 1 to 6 and Comparative Examples 1 to 7 were subjected to 1C charge and 1C discharge cycle tests at a temperature of about 45°C, with a charge and discharge voltage range of about 2.0V to about 4.0V. The number of cycles at 80% SOH obtained in the test is shown in Table 2 below.
[0135] Table 2
[0136]
[0137] From the results of the peeling force test on the negative electrode sheets prepared by the conductive composite binders of Examples 1 to 6 and Comparative Examples 1 to 7 in Table 2, it can be seen that the conductive composite binder of the present invention has excellent bonding strength, which can be attributed to the elastic network structure composed of the natural polysaccharide binder and the conductive self-doped poly (meth) acrylic acid-3-sulfonic acid propyl ester sodium-acrylic acid copolymer, which has more contact points with the active material, and can improve the bonding ability of the binder to the binder, the negative electrode active material and the aluminum current collector.
[0138] From the results of the first coulombic efficiency and DCR tests on the negative electrode sheets prepared by the conductive composite binders of Examples 1 to 6 and Comparative Examples 1 to 7 in Table 2, it can be seen that the conductive composite binder of the present invention can fill the unfavorable pores on the surface of the porous hard carbon, improve the convective conductivity of the electrode material, effectively improve the ion conductivity of the binder through the surface group, greatly reduce the battery charge transfer impedance, improve the current uniformity of the negative electrode surface, induce the formation of a more uniform SEI on the negative electrode surface, and significantly improve the first-cycle coulombic efficiency of the electrode.
[0139] From the results of the high temperature cycle test of the negative electrode sheets prepared by the conductive composite binders of Examples 1 to 6 and Comparative Examples 1 to 7 in Table 2, it can be seen that when the sodium battery is cycled to 80% SOH, Example 1 has the most cycles and the best cycle stability, which further proves that the conductive composite binder obtained by mixing the natural polysaccharide binder with the conductive self-doped poly (meth) acrylic acid-3-sulfonic acid propyl ester sodium-acrylic acid copolymer has an excellent elastic conductive network. At high temperatures, the combined structure of the binder and the active material is relatively stable, which ensures the conductivity between the active material and the current collector, and effectively improves the cycle stability performance of the sodium ion battery.
[0140] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions claimed to be protected by the present invention.
Claims
1. Poly (meth) acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer, characterized in that: The copolymer comprises: Monomer units of formula (I) derived from sodium 3-sulfonyl (meth)acrylate: -(CH2-C(A)(R'))-(I) in, A represents the group -COO-(CH2CH2CH2)-SO3 - Na + , R', independently of one another and identically or differently, represents on each occurrence hydrogen or a methyl group; and The monomer unit of formula (II) derived from an acrylic acid compound: -(CH2-CH(R))-(II) in R, independently of one another and identically or differently, represents on each occurrence a carboxylic acid group, an amide group or a cyano group; in In the poly (meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer, the molar ratio of the monomer unit of formula (I) to the monomer unit of formula (II) is in the range of 1: (0.2-5).
2. The copolymer according to claim 1, characterized in that The weight average molecular weight of the copolymer is in the range of 10,000 to 2,000,000 g / mol; and / or The copolymer is a random copolymer, a block copolymer or an alternating copolymer.
3. A method for preparing a copolymer according to claim 1 or 2, characterized in that: The method comprises: subjecting an aqueous solution containing sodium 3-sulfonyl (meth)acrylate and an acrylic monomer to copolymerization reaction under the condition of adding an initiator.
4. The preparation method according to claim 3, characterized in that: The acrylic monomer comprises one or more of acrylic acid, acrylamide and acrylonitrile; and / or The molar ratio of the sodium (meth)acrylate-3-sulfonate propyl ester to the acrylic acid monomer is in the range of 1:(0.2-5); and / or The solid content of the aqueous solution comprising sodium 3-sulfonyl (meth)acrylate and acrylic acid monomers is in the range of 10 to 40 wt %; and / or The pH value of the aqueous solution containing sodium 3-sulfonyl (meth)acrylate and acrylic acid monomers is in the range of 6 to 9; and / or The copolymerization reaction is carried out at a temperature of 60 to 80° C. for 4 to 10 hours.
5. The preparation method according to claim 3 or 4, characterized in that: The initiator comprises one or more of ammonium persulfate, sodium persulfate and hydrogen peroxide; and / or The initiator is used in an amount of 8 to 15 wt % based on the weight of the acrylic monomer.
6. A conductive composite adhesive, characterized in that: The conductive composite adhesive comprises: Natural polysaccharides, The poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer according to claim 1 or 2, or the poly(meth)acrylic acid-3-sulfonic acid propyl sodium ester-acrylic acid copolymer prepared according to the preparation method of any one of claims 3 to 5, and water, in The weight ratio of the natural polysaccharide to the sodium poly(meth)acrylic acid-3-sulfonate propyl ester-acrylic acid copolymer is (5-15):(1-3).
7. The conductive composite adhesive according to claim 6, characterized in that: The natural polysaccharide comprises one or more of sodium alginate, gum arabic and guar gum; and / or The weight average molecular weight of the natural polysaccharide is in the range of 50,000 to 800,000 g / mol.
8. The conductive composite adhesive according to claim 6, characterized in that: The solid content of the conductive composite adhesive is in the range of 6 wt % to 12 wt %.
9. A sodium ion battery negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector, a negative electrode material, a conductive agent and a conductive composite binder according to any one of claims 6 to 8, and the amount of the conductive composite binder is 1 wt % to 5 wt % based on the total weight of the negative electrode material, the conductive agent and the binder.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Potassium and sodium-containing mixed chlorine salt potassium and sodium separating method
CN109574042A
Binder, negative plate and sodium ion battery
CN116656277A
Water-based copolymer binder, preparation method and sodium ion battery negative electrode material
CN117186812A
Binder for sodium ion battery and preparation method of binder
CN117467380A